2014
DOI: 10.1155/2014/327368
|View full text |Cite
|
Sign up to set email alerts
|

Digital Device in Postextraction Implantology: A Clinical Case Presentation

Abstract: Aim. The aim of this work is to describe a case of immediate implant placement after extraction of the upper right first premolar, with the use of CAD/CAM technology, which allows an early digital impression of the implant site with an intraoral scanner (MHT 3D Progress, Verona, Italy). Case Report. A 46-year-old female was referred with a disorder caused by continuous debonding of the prosthetic crown on the upper right first premolar. Clinically, there were no signs, and the evaluation of the periapical radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The use of the digital method decreases session time since prostheses can be fabricated more rapidly than with the conventional impression technique [ 21 ], thereby increasing patient’s acceptance of the impression procedure [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the digital method decreases session time since prostheses can be fabricated more rapidly than with the conventional impression technique [ 21 ], thereby increasing patient’s acceptance of the impression procedure [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, digital procedures also present some disadvantages [ 20 , 21 ], as for instance the necessity of establishing a learning curve before obtaining satisfactory results. A further disadvantage is represented by the high cost of the devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyetheretherketone (PEEK) has recently attracted considerable attention due to its esthetic properties and has been successfully introduced into the dental field [ 1 , 4 ]. PEEK is very useful in digital dentistry [ 6 ] and in general when immediate loading [ 7 ] or preimplant surgery procedures [ 7 , 8 ] are requested; moreover, PEEK displays good shock absorption and fatigue and abrasion resistance and is highly stable in the oral cavity without undergoing physicochemical changes [ 2 , 4 , 9 ]. Additionally, PEEK overcomes the problems caused by the brittle properties of ceramic materials and artificial techniques, such as staining, which can adjust the final color, thereby conquering the unpleasing appearance of alloy materials [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of IOS has facilitated the use of digital workflows for the fabrication of implant-supported prostheses not only for single missing teeth, but also for multiple missing teeth [ 4 , 5 ]. The benefits of using IOS include reduced patient discomfort, shorter chair time, shorter prosthesis fabrication time, and the ability to store patients’ biometric information as data [ 6 , 7 ]. However, only a few clinical studies have reported on the utility of IOS for implant-supported prosthetic treatment.…”
Section: Introductionmentioning
confidence: 99%